The Influence of Social Media on Students' Mathematical Communication Skills in Mathematics Learning - Machrani Adi Putri Siregar; Izwita Dewi; Hamidah Nasution (MASI Mandiri Edukasi, 2026)
This study aims to analyze the effect of social media use on students' mathematical communication skills. It employs a quantitative approach with a quasi-experimental design (non-equivalent control group design). The sample consisted of 60 eighth-grade students, divided into an experimental group and a control group. The experimental group received social media-assisted mathematics learning, while the control group received traditional instruction. The research instruments included a questionnaire on social media use and a mathematical communication skills test. The questionnaire used a 1-to-5 Likert scale, while the mathematical communication skills test was assessed using a rating scale with scores categorized into three levels: high, medium, and low, defined by intervals of values. Data analysis was performed using simple linear regression and a comparison of means between the two groups. This analysis was conducted using SPSS software. The results showed a significant difference in average mathematical communication skills between the experimental and control groups . Inferential analysis revealed that social media use had a significant effect on students' mathematical communication skills. Furthermore, regression analysis showed that social media use contributed 27.4% to the development of students' mathematical communication skills, with the remainder influenced by other factors external to the study. These results indicate that social media can be a promising pedagogical tool for improving mathematical communication skills through interaction, collaboration, and the interactive exchange of information. Therefore, integrating social media into mathematics learning could create a more communicative and participatory learning environment.